Population education and family planning - Sinha, P. N. (Purnendu Narayan); India Health Foundation (New Delhi : Authors Press, under the auspices of India Health Foundation, 2000)
In the Indian context
Includes bibliographical references and index
Keywords: Population -- Study and teaching -- India; Family policy -- India; Family planning -- India